Analyzing the Factors Influencing Generation z Students’ Entrepreneurial Interest at Universitas Jambi Using SEM-PLS - Sarmada Sarmada; Gusmanely. Z; Yuliana Safitri; Cut Multahadah; Nabilah Shahadah (Jurusan Matematika FMIPA UNM, 2026)
Unemployment is one of the most serious issues facing Indonesia and must be addressed promptly, as it has a direct impact on public welfare and economic growth. This challenge is also evident in Jambi Province, which continues to face difficulties in providing sufficient employment opportunities for its residents. A key solution to reducing unemployment is to encourage entrepreneurship among Generation Z—who are creative, innovative, and capable of leveraging digital technology to create new business opportunities. This study aims to analyze the factors influencing entrepreneurial interest among students at the University of Jambi using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The research employed a quantitative survey method, with data collected through a Likert-scale questionnaire. The exogenous variables examined include social and family environment, innovation and creativity, and technology. The Entrepreneurial interest serving as the endogenous variable. The results of the analysis indicate that all exogenous variables have a significant effect on entrepreneurial interest, with an R² value of 0.59. It is means that 59% of the variation in entrepreneurial interest can be explained by the model. Innovation and creativity were found to have the most dominant influence, with a parameter value of 0.352. These findings highlight the importance of strengthening innovation and creativity in fostering students’ entrepreneurial interest.